Efecto de biofertilizantes y biochar sobre el crecimiento inicial y calidad de plántulas de balsa (Ochroma pyramidale) - Moreira Gaón, Daniela Mercedes (2022)
Balsa (Ochroma pyramidale) is one of the few fast-growing native species of pioneer trees, with both economic and ecological importance. Biofertilizers and also biochar enhance the growth and productivity of forestry, fruit trees and other species, increase biomass production and also provide greater resilience against pest and disease attacks. The objective of the research was to evaluate the effect of biofertilizers and biochar on the initial growth and quality of balsa (Ochroma pyramidale) seedlings. A completely randomized design (DCA) was used with 7 treatments plus a control and 3 repetitions, with a total of 24 experimental units, an analysis of variance (ADEVA) was performed. The registered variables were plant height, dry weight of the aerial part, fresh weight of the root. Among the treatments evaluated, Trichoderma spp+ biochar and the combination of Bacillus subtilis+ Trichoderma spp stood out with the highest growth rate in dry mass with values of 0.15 g respectively in relation to the control. The application of biochar and biofertilizers showed better results, after 40 days a greater role of biofertilizers and their interaction with biochar was evidenced